2019
DOI: 10.1016/j.actamat.2019.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Thick amorphous complexion formation and extreme thermal stability in ternary nanocrystalline Cu-Zr-Hf alloys

Abstract: Building on the recent discovery of tough nanocrystalline Cu-Zr alloys with amorphous intergranular films, this paper investigates ternary nanocrystalline Cu-Zr-Hf alloys with a focus on understanding how alloy composition affects the formation of disordered complexions. Binary Cu-Zr and Cu-Hf alloys with similar initial grain sizes were also fabricated for comparison. The thermal stability of the nanocrystalline alloys was evaluated by annealing at 950 °C (>95% of the solidus temperatures), followed by detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Grain size was calculated from at least 70 grains clearly identified in bright field TEM micrographs by measuring the areas of grains and calculating the average circular equivalent diameter. nm and 5 nm when found at the grain boundary and in the grain interior, respectively, according to prior measurements on these samples from Grigorian and Rupert [62]. The inset in Figure 1 of ZrC precipitates could impact the radiation damage tolerance of the nanocrystalline Cu-Zr samples since precipitates can both limit grain boundary mobility through pinning [39,40] and serve as defect sinks [18,69].…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…Grain size was calculated from at least 70 grains clearly identified in bright field TEM micrographs by measuring the areas of grains and calculating the average circular equivalent diameter. nm and 5 nm when found at the grain boundary and in the grain interior, respectively, according to prior measurements on these samples from Grigorian and Rupert [62]. The inset in Figure 1 of ZrC precipitates could impact the radiation damage tolerance of the nanocrystalline Cu-Zr samples since precipitates can both limit grain boundary mobility through pinning [39,40] and serve as defect sinks [18,69].…”
Section: Methodsmentioning
confidence: 54%
“…Past studies have shown that AIFs tend to form at grain boundaries with high relative solute excess [58]. Since high energy grain boundaries may accommodate more solute segregation [59,60], and ball-milled nanocrystalline metals have been shown to have a higher grain boundary energy than a fully-equilibrated high angle grain boundary [61], it is expected (and has been confirmed multiple times [34,56,62]) that AIFs can readily form in this ball milled nanocrystalline alloy.…”
Section: Methodsmentioning
confidence: 67%
“…The thickness and stability of AIF are mainly dependent on chemical complexity at GB, i.e., increasing the chemical complexity can increase the thickness and stability of AIF. For example, the AIF thickness in Cu-Zr-Hf ternary alloy is larger than that in Cu-Zr binary alloy ( Figure 2 ) [ 86 , 92 ]. It is worth mentioning that the crystalline–amorphous nanocomposites synthesized by amorphous GB complexion generally exhibit high thermal stability [ 93 , 94 ], because amorphous GB complexion can extensively inhibit grain growth of NC metals by reducing GB energy and kinetically slowing GB migration based on solute drag.…”
Section: Characteristic Microstructuresmentioning
confidence: 99%
“…Using traditional thin-film approaches and mechanical milling pathways, researchers have exploited these findings to engineer ''thermally stable'' nanocrystalline systems that employ both thermodynamic and kinetic pathways to minimize the grain boundary energy and/or kinetically pin the boundaries with solutes or nanoclusters [85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] or a harder grain boundary phase. [83,100,101] These all serve to increase the alloy's stability against grain growth at high homologous temperatures (> 0.5 T/T m ) or, in some cases, suppress detrimental phase transformations, [102] besides also imparting many other exceptional mechanical properties. [103][104][105][106][107] A recent perspective piece by Spearot et al [108] specifically speaks to the mechanical properties of stabilized fcc metals, and some unexplored future research needs and opportunities.…”
Section: Low On Energy: Thermodynamic (And Kinetic) Pathways To mentioning
confidence: 99%